Dampak Automatic Teller Machine Dan Mobile Banking Dalam Menarik Minat Nasabah - Aris Munandar; Sukandi Sukartaatmadja; Stanislaus Bandung Argoputro (Jurnal Informatika Kesatuan, 2023)
Information technology is experiencing rapid development, especially in the banking sector in its products and service systems. Automatic Teller Machine (ATM) and Mobile Banking (M-Banking) are supporting the development of technology and information in banking services. Therefore, to attract customers, banks need to increase customer confidence in banking services, especially the use of E-Banking facilities in Automatic Teller Machine (ATM) and Mobile Banking (M-Banking). The purpose of this study is to determine the effect of the Automatic Teller Machine and Mobile Banking together in attracting customers' interest in Bank Rakyat Indonesia Bogor and also to find out what factors influence customer interest in the use of Automatic Teller Machines and Mobile Banking in PT. Bank Rakyat Indonesia (BRI) Bogor. This type of research is a qualitative research that is quantified, using a non-probability sampling technique with accidental sampling method. Using the Solvin approach in determining the number of samples. The data collection method is using a questionnaire. And the data testing method is using the validity test, reliability test, and classical assumption test. includes normality test, multicollinearity, and heteroscedasticity test. For data analysis method using multiple linear test. And hypothesis testing using simultaneous test, partial test, test of determination. In the results of the preparation of this thesis, it can be seen that the effect of Automatic Teller Machine and Mobile Banking in Attracting Customer Interest at Bank Rakyat Indonesia Bogor has a significant influence and also valid testing in attracting customer interest. Through the role of Automatic Teller Machine and Mobile Banking, customers can fulfill their needs. especially through the use of Automatic Teller Machines and Mobile Banking in the process of transaction activities quickly, precisely and safely. So from the preparation of this thesis the researcher can conclude that the influence of Automatic Teller Machine and Mobile Banking in Increasing Customer Interest at Bank Rakyat Indonesia (BRI) Bogor, where the Automatic Teller Machine and Mobile Banking variables can be a liaison in terms of attracting customers' interest in the activity process. transaction. Keywords: Automatic Teller Machine, Mobile Banking, Customer Interest.